ESTIMASI MATRIKS TRANSAKSI ANTAR SEKTOR TAHUN 2020 DI PROVINSI BANTEN - FAJAR, MUHAMMAD (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2021)
Due to the need for up-to-date economic indicators and data, estimates need that reflect regional economic conditions during the COVID-19 pandemic. Therefore, the purpose of this paper is to produce an estimate of the inter-sectoral transaction matrix (as part of the input-output table). The data used in this study are input-output tables in 2016 and GRDP in 2020, source from the Statistics Agency of Banten Province. The method used for estimation is the matrix transformation technique. The results of this study that the matrix transformation technique (MTT) method is easy to apply with limited data. The inter-sector transaction matrix estimated by the MTT can absorb the latest information. Although, there is still old information about the structure contained therein. Based on the comparison between the 2020 inter-sectoral transaction matrix and the 2016 inter-sector transaction matrix. It shows that the impact of COVID-19 has reduced production performance in various sectors.